2016
DOI: 10.11646/zootaxa.4208.6.7
|View full text |Cite
|
Sign up to set email alerts
|

Replacement names for two homonyms of Liothrips brevitubus Karny: one from California, the other for a species damaging Jatropha crops in Mexico

Abstract: There are nearly 280 species of Liothrips listed from around the world (ThripsWiki 2016), all of them presumably feeding and breeding on the leaves of higher plants, and sometimes inducing or being associated with galls (Mound 1994). Despite this, for most of these species the identity of the plant species on which they are dependent is rarely known, and a particularly high proportion of the species are based on few specimens or even single individuals (cf Table 1). As a result, the identity of many of these n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Samples of this species have been studied (in ERMR) from Florida (Orlando) and South Carolina (Colleton Cty), also (in USNM) from Ft Garland (Colorado). However, a few unidentified specimens mentioned by Mound et al (2016) that were collected from Jatropha curcas at Chiapas, Mexico can now be identified as this species, together with 50 specimens representing both sexes collected by Francisco Infante in March and April, 2014, at various sites in the Southern parts of Chiapas State. The species confusus was based on a single female from Homestead, Florida (in USNM), and placed in a key between mali and macroocellatus.…”
Section: Leptothrips Macroocellatus Watsonmentioning
confidence: 94%
“…Samples of this species have been studied (in ERMR) from Florida (Orlando) and South Carolina (Colleton Cty), also (in USNM) from Ft Garland (Colorado). However, a few unidentified specimens mentioned by Mound et al (2016) that were collected from Jatropha curcas at Chiapas, Mexico can now be identified as this species, together with 50 specimens representing both sexes collected by Francisco Infante in March and April, 2014, at various sites in the Southern parts of Chiapas State. The species confusus was based on a single female from Homestead, Florida (in USNM), and placed in a key between mali and macroocellatus.…”
Section: Leptothrips Macroocellatus Watsonmentioning
confidence: 94%
“…Our model for this study is Liothrips jatrophae (Mound et al ., 2016) (Thysanoptera: Phlaeothripidae), which was described as damaging leaves of Jatrophae curcas L. (Euphorbiaceae) (Mound et al ., 2016). However, nothing is known of the chemical ecology of L. jatrophae , except that when it is disturbed, it moves its abdomen from side to side, lifting the tip and it excretes a tiny anal droplet (personal communication).…”
Section: Introductionmentioning
confidence: 99%